Synthesis of the bio-based polyester poly(propylene 2, 5-furan dicarboxylate). Comparison of thermal behavior and solid state structure with its terephthalate and naphthalate homologues. (7th April 2015) - Papageorgiou, George Z.; Papageorgiou, Dimitrios G.; Tsanaktsis, Vasilios; Bikiaris, Dimitrios N.
Abstract: Poly(propylene-2, 5-furan dicarboxylate) (PPF) is a new alipharomatic polyester which can be prepared from monomers derived from renewable resources and efforts are currently being made in order to use PPF as a replacement for its terephthalate (PPT) and naphthalate (PPN) homologues. For this reason, an in-depth comparative study of its thermal behavior and solid state structure was performed in the current manuscript. Conventional and temperature-modulated differential scanning calorimetry were utilized for the evaluation of the different characteristics and behavior of the samples under study. Regarding the structural characteristics, it was found that the different structural rings and the ultimate chain rigidity of the samples play a major role on their final properties. On this basis, the more rigid PPN exhibited higher glass transition temperature and thermal stability than PPF and PPT, as the results suggest. The equilibrium melting point of PPF was found equal to 199 °C, while the heat of fusion of pure crystalline PPF was 141.75 J/g or 27.8 kJ/mol. The spherulitic morphology was also investigated by means of polarized optical microscopy and it was found that PPF forms smaller spherulites than its other two homologues. Graphical abstract: Highlights: Poly(propylene 2, 5-furan dicarboxylate) (PPF) is a new biobased polyester. It can be prepared from monomers derived from renewable resources. The equilibrium melting point of PPF was found 199 °C. The heat of fusion for the crystalline PPF was estimated to be about 141.75 J/g. The thermal stability of PPF is comparable to those of PPT and PPN.